1967
DOI: 10.1530/jrf.0.0140415
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Abnormalities in Rabbit Blastocysts Following Delayed Fertilization

Abstract: Rabbits were mated at timed intervals after an ovulationinducing injection of chorionic gonadotrophin. Blastocysts were recovered at autopsy 6 days after mating and examined cytogenetically for chromosome abnormalities. A marked decrease in the number of blastocysts recovered occurred at delayed ovulation-mating time intervals greater than 10 hr. Thirteen chromosome aberrations arose among 135 blastocysts examined. Triploidy was the commonest anomaly and was found in six instances from rabbits mated 8 and 9 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…However, in agreement with Shaver & Carr (1967, 1969, 8 h delay gave a relatively high yield of triploids (3-13%), though not so high as reported by them (12-5% after 6-9 h delay).…”
Section: (Iii) Properties Of the M-markersupporting
confidence: 87%
See 2 more Smart Citations
“…However, in agreement with Shaver & Carr (1967, 1969, 8 h delay gave a relatively high yield of triploids (3-13%), though not so high as reported by them (12-5% after 6-9 h delay).…”
Section: (Iii) Properties Of the M-markersupporting
confidence: 87%
“…In the rabbit, the M-marker segregations showed that nearly all triploidy after 8 h delayed insemination was digynic. The 12 XXX and 24 XXY were in a proportion deviating significantly from the digynic expectation of 50:50 at the time of fertilization (Shaver & Carr (1967,1969 report 3 XXX, 7 XXY after 6-9 h delay). This suggests a higher relative viability of XXY, but a detailed quantitative check on the lines of Beatty (1978) cannot be made until more data are available.…”
Section: (V) the Relative Viability Of XXX And Xx Y Triploidsmentioning
confidence: 75%
See 1 more Smart Citation
“…Hsu et al (1975) have concluded that although the most obvious secondary con strictions are equivalent to NORs which are in turn equivalent to sites of rDNA, second ary constrictions are not absolutely equated with NORs. In the rabbit, secondary con strictions have been reported on medium to small-sized metacentric chromosomes (Prunieras et al, 1965;Shaver, 1968) in addi tion to the subtelocentric and acrocentric chromosomes 13, 16, and 20 which stain with silver.…”
mentioning
confidence: 99%
“…After size determina¬ tion, by a filar micrometer eyepiece, the blastocysts were separately placed in fresh culture medium to which colchicine (0-5 µg/ml) had been added. Following incubation for \\ hr at 37°C in 5% C02 in air, chromo¬ some preparations were made by a modification of the method of Shaver & Carr (1967 Nichols, Levan, Hansen-Melander & Melander (1965). The numbering of the autosomal pairs followed that of Shaver & Carr (1967).…”
mentioning
confidence: 99%